Atmospheric nonequilibrium mini-plasma jet created by a 3D printer - Toshihiro Takamatsu; Hiroaki Kawano; Hidekazu Miyahara; Takeshi Azuma; Akitoshi Okino (AIP Advances, 2015)
In this study, a small-sized plasma jet source with a 3.7 mm head diameter was created via a 3D printer. The jet’s emission properties and OH radical concentrations (generated by argon, helium, and nitrogen plasmas) were investigated using optical emission spectrometry (OES) and electron spin resonance (ESR). As such, for OES, each individual gas plasma propagates emission lines that derive from gases and ambient air inserted into the measurement system. For the case of ESR, a spin adduct of the OH radical is typically observed for all gas plasma treatment scenarios with a 10 s treatment by helium plasma generating the largest amount of OH radicals at 110 μM. Therefore, it was confirmed that a plasma jet source made by a 3D printer can generate stable plasmas using each of the aforementioned three gases.